PERILAKU BEKERJA DARI RUMAH PARA PEGAWAI DI SEKTOR PUBLIK SELAMA PANDEMI COVID-19: Literature Review - Taufik Taufik; Wayu Eko Yudiatmaja; Muhamad Rajab (Journal Publicuho, 2022)
The main purpose of this paper is to review the current literature on public employees’ behavior for work from home during the COVID-19 pandemic. Specifically, we develop conceptualization and hypothesis development of public employee’s behavior for work from home utilizing theory of planned behavior (TPB). Using a qualitative literature review, we establish five hypotheses regarding the association of attitude, subjective norms, perceived behavioral control, and understanding on intention and behavior. To examine the model, it can be tested by scholars in empirical research.